Tinjauan Yuridis Terhadap Pemalsuan Identitas dalam Perkawinan - Berutu, Sigar P; Nadeak, Uli Monica Angelina; Sidebang, Clara Erlika; Tinambunan, Enjelina; Nainggolan, Samuel Dharma Putra (Universitas Ekasakti, 2024)
This research discusses identity forgery in marriage. Identity forgery is a form of crime that often occurs. The focus of the research raised is: 1) What are the forms of identity falsification in the context of marriage that occur in practice in the community? 2) How is the regulatory and legal framework in Indonesia that regulates cases of identity forgery in marriage? This research uses normative legal research methods, questions are analyzed by combining legal materials (which are secondary data). The conclusions of this research are: It is important to implement security measures and conduct careful identity verification in the context of marriage to prevent cases of identity forgery, it is also important to note that regulations and laws are subject to change, and up-to-date verification from official sources or consultation with legal experts is recommended for a more accurate and up-to-date understanding.